Evaluation of the nutrition-sensitive features of the fourth phase of Ethiopia's Productive Safety Net Programme - Berhane, Guush; Golan, Jenna; Hirvonen, Kalle; Hoddinott, John F.; Kim, Sunny S.; Taffesse, Alemayehu Seyoum; Abay, Kibrewossen; Assefa, Thomas; Habte, Yetimwork; Abay, Mehari Hiluf; Koru, Bethlehem; Tadesse, Fanaye; et al. (International Food Policy Research Institute, 2020)
This study assesses progress in the implementation of the nutrition-sensitive interventions of the fourth phase of Ethiopia’s Productive Safety Net Programme (PSNP-4) and its impact on: (1) the pathways underpinning children’s nutritional status; and (2) the roles it plays in reducing the malign effect of seasonality on the nutritional status of women and pre-school children. The analysis is based on four rounds of household survey data, conducted in March and August 2017 (baseline) and March and August 2019 (endline). These surveys focused on households with a child less than 24 months of age (index child) and his/her mother (index mother). In 2017 and 2019, the survey teams visited more than 2,500 households in 264 kebeles in 88 PSNP woredas in the Amhara, Oromia, SNNP, and Tigray regions.